A new Masdevallia (Orchidaceae: Pleurothallidinae) from the Ecuadorian Amazon foothills of the Llanganates mountains - Gutiérrez Del Pozo, Diego; Jiménez, Marco M.; Vélez-Abarca, Leisberth; Baquero, Luis E. (Phytotaxa, 2022)
A new Masdevallia species from eastern Ecuador, is described, illustrated and compared with similar species. The species is most similar to Masdevallia aphanes; both species are small plants for the genus with weak inflorescences that bear striped flowers with acaudate sepals. The horizontal inflorescences with yellow flowers striped with red-brown and the convex, subpandurate lip of Masdevallia rubileoixchelorum immediately distinguishes it from the similar M. aphanes by the abaxially deep sandal-shaped lip and for the ovary with undulate-dentate ribs which are almost keeled.